The impact of obesity on the risk of developing, activity and treatment outcomes of autoimmune rheumatic diseases - Pysiewicz, Mateusz; Stadnicka, Olga; Knapik, Anna; Brodowska, Anna; Kuś, Justyna; Białowąs, Patrycja; Zięba, Natalia; Czapiński, Olgierd; Tomicka, Ewa; Ciesielski, Maciej (Quality in Sport, 2026)
Background: Obesity is becoming a new epidemic. It is the cause of numerous serious medical complications. Obesity is associated with chronic low-grade inflammation, oxidative stress, and increased expression of pro-inflammatory cytokines and adipokines. Autoimmune rheumatic diseases are driven by similar mediators and immunological dysregulations, which are disturbed in obesity. It suggests potential associations between obesity and these diseases. Aim: The aim of this review is to examine evidence on how obesity affects the risk of developing common rheumatic diseases, the activity/severity of these diseases, and the outcomes of treatment. Material and methods: A literature search was conducted in the PubMed database up to February 2026 using the following terms: “obesity” and “BMI”, in combination with disease-specific keywords. Only articles published in English or with an available English abstract were included. Only studies on humans were included. Meta-analyses and cohort studies were prioritised. Additionally, two relevant conference abstracts [23, 27] that were not indexed as full records in PubMed were identified via manual screening of reference lists and included in the review. The literature selection process and the flow of information at each stage of the review were presented in accordance with the PRISMA guidelines. Conclusions: Obesity increases the risk of development of rheumatoid arthritis and psoriasis and there is some evidence of common genetic backgrounds. Childhood obesity increases the risk of developing systemic lupus erythematosus, whereas the association with adult obesity is less consistent. There are positive correlations between body mass index and disease activity in rheumatoid arthritis, psoriasis and ankylosing spondylitis, as well as with certain clinical manifestations, including lupus nephritis and psoriatic arthritis. Obesity significantly reduces the likelihood of good treatment outcomes with anti-TNF agents.